DISTRIBUSI FLUKS NEUTRON SEBAGAI FUNGSI BURN-UP BAHAN BAKAR PADA REAKTOR KARTINI - Fatkhiyatul Athiqoh; Wahyu Setia Budi; Choirul Anam; Tri Wulan Tjiptono (Youngster Physics Journal, 2014)
The effective multiplication factor (keff) and the flux distribution in the Kartini reactor which used Uranium Zirconium Hydride (UZrH) as fuel, pure water (H2O) as moderators and cooland has been analyzed using Monte Carlo simulation. The flux distribution analyzed by splitting core reactor become 5 rings (B, C, D, E and F). The effective multiplication factor (keff) and flux distribution calculated by MCNP 4C with burn-up variation 0%, 2,5%, 5%, 7,5%, 10%, 12,5%, 15%. The result shows that the critical condition obtained from burn-up rate 0% up to 5%. The highest value of flux distribution in the middle, at ring B and the value gets smaller towards to edge of reactor core.Keywords : flux distribution, keff, MCNP, Kartini reactor